PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP HUBUNGAN ANTARA PERSEPSI PENERAPAN SISTEM E-FILING DENGAN TINGKAT KEPATUHAN WAJIB PAJAK BADAN YANG DIMEDIASI OLEH PERILAKU WAJIB PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Jakarta Pulo Gadung) - Panca Herina, Veronica Nensi (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The purpose of this study is to find empirical evidence on: 1) The effect of perception of the application of e-filing system to taxpayer compliance; 2) Effect of perception of e-filing system implementation on Taxpayer’s behavior; 3) The influence of taxpayers’ behavior on taxpayer compliance; 4) The extent to which usability perception can moderate the relationship between the perception of the application of e-filing system and the compliance level of the Taxpayer; 5) The extent to which perceptions of ease can moderate the relationship between the perception of the application of e-filing system to the level of taxpayer compliance. This type of research is classified as a causal study. The population in this study covers the total number of taxpayers registered in KPP Pratama East Jakarta Pulo Gadung. Sample selection by purposive sampling method. The type of data used is the primary data. Data collection method used is by using questionnaire. The analysis used is path analysis, test of sobel and test of absolute difference value. Result of research indicate, 1) Perception of applying of e-filing system have positive effect to taxpayer compliance; 2) Perception of application of e-filing system has a positive effect on taxpayer behavior; 3) Taxpayers’ behavior has a positive effect on taxpayer compliance level; 4) Usability perception proved to moderate the relationship between perception of e-filing system implementation with Taxpayers compliance level; 5) Perception of ease proved to moderate the relationship between perception of application of e-filing system with taxpayers compliance level.